Prolonged Duration Local Anesthesia by Combined Delivery of Capsaicin- and Tetrodotoxin-Loaded Liposomes. (September 2019) - Shomorony, Andre; Santamaria, Claudia M.; Zhao, Chao; Rwei, Alina Y.; Mehta, Manisha; Zurakowski, David; Kohane, Daniel S.
Abstract : BACKGROUND: Capsaicin, the active component of chili peppers, can produce sensory-selective peripheral nerve blockade. Coadministration of capsaicin and tetrodotoxin, a site-1 sodium channel blocker, can achieve a synergistic effect on duration of nerve blocks. However, capsaicin can be neurotoxic, and tetrodotoxin can cause systemic toxicity. We evaluated whether codelivery of capsaicin and tetrodotoxin liposomes can achieve prolonged local anesthesia without local or systemic toxicity. METHODS: Capsaicin- and tetrodotoxin-loaded liposomes were developed. Male Sprague-Dawley rats were injected at the sciatic nerve with free capsaicin, capsaicin liposomes, free tetrodotoxin, tetrodotoxin liposomes, and blank liposomes, singly or in combination. Sensory and motor nerve blocks were assessed by a modified hotplate test and a weight-bearing test, respectively. Local toxicity was assessed by histologic scoring of tissues at the injection sites and transmission electron microscopic examination of the sciatic nerves. Systemic toxicity was assessed by rates of contralateral nerve deficits and/or mortality. RESULTS: The combination of capsaicin liposomes and tetrodotoxin liposomes achieved a mean duration of sensory block of 18.2 hours (3.8 hours) [mean (SD)], far longer than that from capsaicin liposomes [0.4 hours (0.5 hours)] ( P < .001) or tetrodotoxin liposomes [0.4 hours (0.7 hours)] ( P < .001) given separately with or without the second drug in free solution. This combination caused minimal myotoxicity and muscle inflammation, and there were no changes in the percentage or diameter of unmyelinated axons. There was no systemic toxicity. CONCLUSIONS: The combination of encapsulated tetrodotoxin and capsaicin achieved marked prolongation of nerve block. This combination did not cause detectable local or systemic toxicity. Capsaicin may be useful for its synergistic effects on other formulations even when used in very small, safe quantities.